Chinese herbal formula Tongxie Yaofang granules for diarrhoea-predominant irritable bowel syndrome: a randomised, double-blind, placebo-controlled, phase II trial - Liang, Shi-Bing; Cheng, Hong-Jie; Zhang, Qiao-Yan; Han, Mei; Li, Yu-Fei; Cao, Hui-Juan; Yu, Ze-Yu; Kong, Ling-Yao; Cai, Yan-Mei; An, Li-Bao; Zhao, Bao-Tuan; Xu, Shan-Shan; et al. (BMJ open, 2025)
ObjectivesTo assess the therapeutic effects and safety of Tongxie Yaofang (TXYF) granules vs placebo as an alternative treatment for diarrhoea-predominant irritable bowel syndrome (IBS-D). We hypothesised that TXYF would improve clinical responses among patients with IBS-D.DesignA randomised, double-blind, placebo-controlled, phase II, superiority trial.SettingOutpatients attending the Fangshan Hospital, Beijing University of Chinese Medicine, Beijing, China.Participants96 eligible participants included men and women ranging from late adolescence to middle adulthood (18–65 years), diagnosed with IBS-D according to the Rome IV criteria. In addition, they were required to have an irritable bowel syndrome symptom severity score (IBS-SSS) of at least 75.InterventionsTXYF granules (3.7 g) twice daily (taken orally before meals) or placebo for 8 weeks.Primary and secondary outcomesThe primary outcome was the response rate measured by the change in IBS-SSS compared with baseline at week 8. Secondary outcomes included stool frequency; stool consistency at weeks 4, 8 and 20; and quality of life, anxiety and depression at week 8; and safety was monitored throughout the trial.ResultsThe TXYF and placebo groups each comprised 48 participants. The response rate was not significantly different at week 8 between the two groups (the unadjusted treatment effect estimate (intention-to-treat analysis) was 1.12 (95% CI (0.89, 1.41)), p=0.348). Both groups had a high and similar rate of symptom reduction (79.2% (38/48) vs 70.8% (34/48)). There were no statistically significant differences between the two groups on secondary outcomes, although both groups showed substantial improvements. Adverse events in the TXYF and placebo groups were one (sinus arrhythmia) and two (elevated transaminases, weakly positive faecal occult blood), respectively. No serious adverse events occurred.ConclusionsDespite showing clinically meaningful improvements in IBS-D symptoms and a reasonable safety profile after 8 weeks, no significant differences were observed between the TXYF and placebo groups. This suggests that the severity of IBS-D symptoms in both treatment arms might have decreased over time, regardless of the treatment, and highlights the need to investigate the relationship between IBS-D and patient psychology. Future large-scale, rigorously designed trials with longer treatment and follow-up periods are essential to evaluate the therapeutic effects and safety of TXYF, and to explore the psychological factors.Trial registration numberISRCTN12453166.